Formerly Abducted Child Mothers in Northern Uganda: A Critique of Modern Structures for Child Protection and Reintegration - Awich Ochen, Eric; Adele D., Jones; Mcauley, James W. (Journal of Community Practice, 2012)
The study documents and analyzes the community structures supporting reintegration of the formerly abducted child mothers (FACM) within post-conflict northern Uganda. A qualitative approach assesses the relevance and effectiveness of child protection structures created by different development agencies to enhance the reintegration of FACM and protect vulnerable children more broadly. Findings suggest that the efficacy of the community-based structures to support the reintegration efforts have been hampered by the creation of competing structures by the different non-governmental organizations (NGOs) and major development organizations such as UNICEF. The limited community ownership of these structures and the inadequate psychosocial training of child protection workers are problematic in meeting the needs of formerly abducted child mothers. Other constraining factors are the limited government role in supporting these child protection structures, the challenge of adapting the structures to the new post-active conflict development context, and limited outreach to FACM. These factors limit the prospects for supporting formerly abducted children and sustaining structures within the community once agencies and donor support is withdrawn. The key lesson for social work practice and social development in Africa is that effective interventions at supporting the reintegration of children affected by armed conflict need to consider the importance of indigenous institutions and structures within the implementation areas.
Keywords: Child protection; Reintegration; Child mothers; Abduction; Armed conflict; Armed conflict